Christians in the wake of the sexual revolution recovering our sexual sanity - Alcorn, Randy C. (Portland, OR Multnomah, 1985)
Includes bibliographical references and indexes.
Keywords: Sex -- religious aspects -- Christianity; Sexual ethics